Dedifferentiated early postnatal lung myofibroblasts redifferentiate in adult disease - Chandran, Rachana R.; Adams, Taylor S.; Kabir, Inamul; Gallardo-Vara, Eunate; Kaminski, Naftali; Gomperts, Brigitte N.; Greif, Daniel M. (Frontiers in Cell and Developmental Biology, 2024)
Alveolarization ensures sufficient lung surface area for gas exchange, and during bulk alveolarization in mice (postnatal day [P] 4.5–14.5), alpha-smooth muscle actin (SMA)+ myofibroblasts accumulate, secrete elastin, and lay down alveolar septum. Herein, we delineate the dynamics of the lineage of early postnatal SMA+ myofibroblasts during and after bulk alveolarization and in response to lung injury. SMA+ lung myofibroblasts first appear at ∼ P2.5 and proliferate robustly. Lineage tracing shows that, at P14.5 and over the next few days, the vast majority of SMA+ myofibroblasts downregulate smooth muscle cell markers and undergo apoptosis. Of note, ∼8% of these dedifferentiated cells and another ∼1% of SMA+ myofibroblasts persist to adulthood. Single cell RNA sequencing analysis of the persistent SMA− cells and SMA+ myofibroblasts in the adult lung reveals distinct gene expression profiles. For instance, dedifferentiated SMA− cells exhibit higher levels of tissue remodeling genes. Most interestingly, these dedifferentiated early postnatal myofibroblasts re-express SMA upon exposure of the adult lung to hypoxia or the pro-fibrotic drug bleomycin. However, unlike during alveolarization, these cells that re-express SMA do not proliferate with hypoxia. In sum, dedifferentiated early postnatal myofibroblasts are a previously undescribed cell type in the adult lung and redifferentiate in response to injury.